Sonoelastography in the diagnosis of breast mass: an extended armamentarium - Kannappan, K. Manickkam; Dev, Bhawna; Ramakrishnan, Ramya (International Surgery Journal, 2018)
Background: To presenting with breast lumps are very common in surgical practice and the routine use of ultrasound in the diagnosis is well validated. But there are gray zones in equivocal cases which increase the number of negative biopsies. To increase the sensitivity and specificity of ultrasound by adding another non-invasive modality, namely strain elastography, can reduce this rate. To evaluate the sensitivity and specificity of strain elastography in the diagnosis of breast masses. Methods: As part of the triple assessment patients presenting with breast lumps underwent ultrasonography and strain elastography, where strain ratios were calculated. Based on which they either underwent percutaneous biopsy or surgical excision. A total of 30 patients with breast lesions underwent sonomammogram in which the breast lesions were both graded with BIRADS and also the elastography and strain ratio was calculated. Results: Strain ratio has higher sensitivity and specificity which makes it a valid diagnostic tool in the evaluation of breast masses. Conclusions: It can also help in reducing the number of benign lesion biopsies and also reduce the number of negative biopsies. Being a non-invasive modality, it is much more patient compatible and economically cheaper when compared with MRI and modalities.